Dampak Pembelajaran KWL (Know, Want To Know, Learned) Berbantuan Buku Cerita Untuk Meningkatkan Minat Membaca Ditinjau Dari Motivasi Belajar - Ratu Bulkis Ramli; Sri Hanipah; Paskha Marini Thana; Wahyuniar Wahyuniar (Universitas Palan, 2023)
The ability to read and foster an interest in reading in children is an effort to improve educational standards while at the same time forming a child's personality with character. The purpose of this study was to determine the significant impact of the storybook-assisted KWL (Know Want to Know Learned) strategy in terms of the learning motivation of class XI students of SMAN 2 Merauke. This type of research uses the Non-Equivalent posttest only control group design. A total of 50 students were sampled in this study, 25 students in the experimental class and 25 students in the control class. Research data collection was carried out by non-test method using observation sheets. Manova as a data analysis method used in this study. The results showed that the KWL (Know Want to Know Learned) strategy, with the help of story books, had an impact on reading interest and learning motivation. The results of the study showed a significant difference. The results of the analysis also show that, when compared with reading interest, learning motivation is the variable that is more influenced. Therefore, the KWL (Know Want to Know Learned) strategy with the help of story books can be suggested as an innovative way of learning to increase reading interest and motivation to learn